Profile Aspects of Graphic Education at Polytechnic University - Irina D. Stolbova; Evgeniya P. Aleksandrova; Lyudmila V. Kochurova; Konstantin G. Nosov (Высшее образование в России, 2019)
Availability of qualified engineering personnel for high-tech industries is a topical problem today. To close the gap between the practice of polytechnic education and real engineering activities, it is necessary to introduce innovative educational technologies aimed at developing students’ ability to work in a team, competences in the field of modern information and communication technologies, as well as a willingness to carry out design based on spatial modeling.Within the framework of subject training, it is necessary to ensure the unity of fundamental (generalized, theoretical) knowledge and special knowledge corresponding to the profile of the training area. An appropriate construction of the training program contributes to the adaptation and concretization of subject competencies in the direction required for this engineering specialty.Graphic training is the first professionally oriented discipline at technical university. Within the framework of subject training, it is important to create a learning environment that is close to professional. The authors adduce the examples of educational tasks based on the method of projects and corresponding to the profile of the educational program that students perform in the course of self-directed work. An innovative aspect in the development of individual tasks is the ability to perform projects in 3d.